Microstructure characterization of different types of chlamydospores in Arthrobotrys flagrans - Wang, Bo‐bo; Wang, Feng‐hui; Wang, Yu‐jue; Jia, Yi‐bo; Tian, Shu‐yue; Zhang, Xi‐chen; Xue, Ya‐juan; Li, You‐lei; Cai, Kui‐zheng (Journal of basic microbiology, 2024)
The morphological and structural differences of different types of chlamydospore of Arthrobotrys flagrans, a nematophagous fungus, were studied under light microscope and electron microscope to provide a reference for the biological control of parasitic nematodiasis. In this study, A. flagrans isolate F088 dormant chlamydospore and nondormant chlamydospore were selected as the research objects. The structural differences of these spores were observed by optical microscopy through lactol cotton blue, Trypan blue, and 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT) staining. FunXite ‐1, 4',6‐diamidino‐2‐phenylindole, and calcofluor white staining were used to observe the metabolic activity, cell wall, and nucleus differences of the two types of spores under fluorescence microscope. Ultrastructure of the two kinds of spores was observed using scanning electron microscope (SEM) and transmission electron microscope (TEM). Since lacto phenol cotton blue, trypan blue staining cannot distinguish dormant spores from dead spores, MTT assay was performed. Fluorescence microscopy observation showed that the cytoplasmic metabolic activity of nondormant spores was stronger than that of dormant spores. The nucleus of dormant spores was bright blue, and their fluorescence was stronger than that of nondormant spores. The cell wall of nondormant spores produced stronger yellow‐green fluorescence than that of dormant spores. Ultrastructural observation showed that there were globular protuberances on the surface of the two types of spores but with no significant difference between them. The inner wall of dormant spore possesses a thick zona pellucida with high electron density which was significantly thicker than that of nondormant spores, and their cytoplasm is also changed. In this study, the microstructure characteristics of dormant and nondormant chlamydospores of A. flagrans fungi were preliminarily clarified, suggesting that the state of cell wall and intracellular materials were changed after spores entered to dormancy.